Finite element modelling of laterally loaded piles in a dense marine sand at Dunkirk - Taborda, DMG; Zdravkovic, L; Potts, DM; Burd, HJ; Byrne, BW; Gavin, KG; Houlsby, GT; Jardine, RJ; Liu, T; Martin, CM; McAdam, RA (ICE Publishing, 2019)
The paper presents the development of a three-dimensional finite-element model for pile tests in dense Dunkirk sand, conducted as part of the PISA project. The project was aimed at developing improved design methods for laterally loaded piles, as used in offshore wind turbine foundations. The importance of the consistent and integrated interpretation of the soil data from laboratory and field investigations is particularly emphasised. The chosen constitutive model for sand is an enhanced version of the state parameter-based bounding surface plasticity model, which, crucially, is able to reproduce the dependency of sand behaviour on void ratio and stress level. The predictions from three-dimensional finite-element analyses, performed before the field tests, show good agreement with the measured behaviour, proving the adequacy of the developed numerical model and the calibration process for the constitutive model. This numerical model directly facilitated the development of new soil reaction curves for use in Winkler-type design models for laterally loaded piles in natural marine sands.